2002
DOI: 10.1021/ja026279w
|View full text |Cite
|
Sign up to set email alerts
|

The Elusive Oxidant Species of Cytochrome P450 Enzymes:  Characterization by Combined Quantum Mechanical/Molecular Mechanical (QM/MM) Calculations

Abstract: The primary oxidant of cytochrome P450 enzymes, Compound I, is hard to detect experimentally; in the case of cytochrome P450(cam), this intermediate does not accumulate in solution during the catalytic cycle even at temperatures as low as 200 K (ref 4). Theory can play an important role in characterizing such elusive species. We present here combined quantum mechanical/molecular mechanical (QM/MM) calculations of Compound I of cytochrome P450(cam) in the full enzyme environment as well as density functional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
405
2
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 299 publications
(466 citation statements)
references
References 52 publications
52
405
2
6
Order By: Relevance
“…However, the hydrogen bond between the sulfur and the Q360 backbone hydrogen elongates after MD followed by QM(B3LYP)/MM optimization. 25 The large flexibility of M445, in CYP3A4, manifested in all MDs is not associated with sulfur spin density variations. Coupled with the fact that in the initial structure the NH---S bond has an angle of 82°, which is not favored for a hydrogen bond we conclude that in contrast to CYP cam , the M445 residue in the CYP3A4 does not influence to a large extent the electronic structure of the thiolate ligand of Cpd I.…”
Section: Sulfur H-bonding Network and Ligand Influencementioning
confidence: 91%
“…However, the hydrogen bond between the sulfur and the Q360 backbone hydrogen elongates after MD followed by QM(B3LYP)/MM optimization. 25 The large flexibility of M445, in CYP3A4, manifested in all MDs is not associated with sulfur spin density variations. Coupled with the fact that in the initial structure the NH---S bond has an angle of 82°, which is not favored for a hydrogen bond we conclude that in contrast to CYP cam , the M445 residue in the CYP3A4 does not influence to a large extent the electronic structure of the thiolate ligand of Cpd I.…”
Section: Sulfur H-bonding Network and Ligand Influencementioning
confidence: 91%
“…The resulting system (protein in a water droplet, overall hydration shell thickness 12 Å) consisting of 81,587 atoms (24,622 water molecules, 7,721 atoms in the protein) was energyminimized in CHARMM (adopted basis Newton-Raphson method). In this and the subsequent steps, the following constraints were applied: the outer 6 Å of water hydration shell, the oxoferryl heme (porphyrine ring, iron, and oxygen atoms) were fixed, soft restrains were applied to the distances from thiolate to the NH-backbone groups of the three residues after the coordinating cysteine [values according to Shaik et al (21)]. …”
Section: Chemicals and Reagents Ellipticine Nadpmentioning
confidence: 99%
“…Shaik et al reported from QM/MM calculations that the inclusion of hydrogen bonds to the axial ligand transforms the electronic structure of compound I from a sulfur-centered radical to a porphyrin centered radical cation. 21) They have shown that the FeO unit remains with a spin density of about 2.0 even if its electronic structure is changed in a fashion similar to the compound I treated here (see Table 1). …”
Section: Reactant Complexmentioning
confidence: 59%